Autonomic Nervous System in Preterm Very Low Birth Weight Neonates with Intraventricular Hemorrhage - Shiono, Ai; Bonno, Motoki; Toyoda, Hidemi; Ogawa, Masahiro; Tanaka, Shigeki; Hirayama, Masahiro (American Journal of Perinatology, 2022)
Objective Heart rate variability (HRV) indicates cardiac autonomic nerve activity and is influenced by brain damage during the neonatal period. We aimed to determine whether a correlation exists between the HRV of extremely preterm neonates and neurodevelopmental test scores.Study Design Electrocardiogram data of neonates were assessed and HRV patterns in extremely preterm neonates with severe intraventricular hemorrhage (IVH; n = 6) and those with no/mild IVH (n = 28) were compared. We analyzed the relationship between HRV and neurodevelopmental outcomes at 18 months (n = 21) and 3 years (n = 23) in extremely preterm neonates.Results HRV was significantly associated with IVH severity in extremely preterm neonates (p < 0.05). Neonates with severe IVH exhibited increased HR and decreased mean R-to-R interval (NN) compared with neonates with no/mild IVH. HRV parameters significantly decreased in the severe IVH group, but not in the no/mild IVH group, suggesting that both sympathetic and parasympathetic activities decreased in neonates with severe IVH. Additionally, decreased HR and increased NN were significantly related to impaired neurodevelopmental outcomes in the no/mild IVH group at corrected ages of 18 months and 3 years, respectively (all p < 0.05).Conclusion HRV was significantly associated with IVH severity and neurodevelopmental outcome in extremely preterm neonates. HRV can distinguish extremely preterm neonates who subsequently had severe IVH from those who had no/low-grade IVH. HRV may identify extremely preterm neonates needing adjuvant neuroprotective interventions. These findings warrant further investigation in a larger population of extremely preterm neonates.Key Points
Keywords: extremely preterm neonates; heart rate variability; intraventricular hemorrhage; neurodevelopmental impairment